IMPEMENTASI SISTEM EVALUASI DIRI DALAM PENCAPAIAN MUTU LULUSAN SD ASSALAM BANDUNG - Permana, Hidayat Aji; Nugraha, Muhamad Arif; Fachriyah, Neng Vera; Nasir, Tatang Muh; Hatala, Abdul Azis (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
Evaluation is needed to measure the quality of educational institutions, so the prerequisites for measuring these criteria are an internal quality assurance system. The internal quality assurance system is used to answer various problems that exist in educational institutions and to realize the vision and mission of the institution. This study uses a qualitative approach with a qualitative descriptive method. The results of this study indicate that the internal quality assurance process for SD Assalam Bandung begins with the School Self Evaluation (EDS) to measure the effectiveness of each quality achievement of each component of the National Education Standards (NES). Furthermore, efforts to comply with Quality Standards are followed up by the School Education Quality Assurance Team (TPMPS) which is outlined in each planning document for meeting educational standardization, in which various activities, objectives, implementation strategies, indicators of success, and details of the required costs are explained. The quality compliance plan is implemented in every aspect that involves all components in a comprehensive manner. The whole series of implementation of direct mentoring quality fulfillment at TPMPS is then evaluated to see the effectiveness of the implementation of learning. The results serve as a reference for setting new quality standards that are more effective, the mentoring is documented in the form of an SPMI report cardTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//